Dropping out of school: A psychosocial approach - Hilal Meryem; Hicham Khabbache; Driss Ait Ali (Advances in Medicine, Psychology, and Public Health)
Introduction: School dropout is a pervasive issue with complex origins, often resulting from various forms of violence and challenges faced by students within the educational system. This article explores the multifaceted causes of school dropout and proposes a holistic approach to prevent it. Methods: This article, structured as a comprehensive review, draws information from existing literature and research studies on school dropout. It synthesizes findings from diverse sources, including academic journals, sociological studies, and educational psychology literature. The information presented here is based on a thorough analysis and synthesis of existing knowledge in school dropouts. Results: School dropout is not solely the student's decision but is often a consequence of prolonged exposure to subtle forms of violence and challenges within the educational environment. It can lead to various adverse outcomes, including deviant behavior and extremism. Discussion and Conclusion: A proactive approach within the school ecosystem is crucial. Combating school dropout effectively involves improving the quality of life in schools, eliminating violence, and providing specialized support through school psychologists and assistants. Additionally, teacher training, emotional support, and bridging connections with parents from challenging backgrounds are essential components of this comprehensive strategy. By addressing these issues, schools can create a nurturing environment that minimizes the toll of violence and retains students, ultimately contributing to a more successful educational system.